Development Management of Interbank Competition in the Corporate Lending Market - Kretov, Dmitry; Mindova, Olena; Aitaliev, Bakytbek; Koldovskyi, Artem (Dr. Viktor Koval, 2023)
Introduction. The effective functioning of the banking sector is a prerequisite for the economy development   and one of the main sources of providing monetary resources for economic activity of entrepreneurship, regardless of ownership forms and spheres of management. The urgent problem of business development today is the lack of own financial resources for economic activity and a significant reduction in corporate bank lending. Therefore, it is relevant to study and solve the problems of renewing lending by banks to the corporate sector at the present time, taking into account the prevention of the increase in the level of credit risk. Aim and tasks. The purpose of the study is to manage the development of interbank competition in the corporate lending market based on a study of the bank lending state to corporate clients and further prospects in the absence of an accurate forecast of the economic situation in Ukraine. Results. The analysis of the dynamics of the bank lending total volume to business in 2022-2023 and the structure of the provided corporate loans showed that since mid-2022 there has been a tendency to decrease the volume of loans to entrepreneurship, which is caused by a decrease in demand from borrowers and an increase in the cost of credit from banks. In addition, more than 70% of the loans provided are concentrated in five larger banks in Ukraine, including 4 state-owned ones, preferential lending to businesses with state support prevails. To further assess the development of corporate bank lending, a prediction of lending volumes for 2023 was carried out, which made it possible to establish that lending volumes by banks of non-financial corporations have a forecast downward trend. Conclusions.  Recommendations for improving corporate bank lending processes are proposed, namely: development of credit policy directions that will prevent a new crisis of confidence in banks and the banking system; development of measures that will prevent the curtailment of preferential targeted lending programs; developing measures to reduce the level of non-performing loans and solving the problem of lowering the cost of financing sources.